Pengaruh Media Exposure dan Kepemilikan Manajerial terhadap ESG Performance - Lestari, Lidia Ayu; Sebrina, Nurzi (Jurnal Eksplorasi Akuntansi, 2025)
This study aims to analyze the effect of media exposure and managerial ownership on ESG performance. ESG performance is measured by the ESG score issued by Refinitiv Eikon. Media exposure is measured using the Janis-Fadner Coefficient. Managerial ownership is measured by the number of shares owned by management compared to the number of shares outstanding. This research is causality research with a quantitative approach. The object of this research is all companies listed on the Indonesia Stock Exchange (IDX) in 2020-2023 using a sampling method, namely purposive sampling so that the final sample of this study was 172 with 43 companies during the 4 year research period. In conducting hypothesis testing, this study uses panel data regression analysis using Eviews software version 12. Overall, the results of this study indicate that media exposure in high profile companies has a positive effect on ESG performance, while low profile companies have no effect on ESG performance. Managerial ownership of high profile and low-profile companies has no effect on ESG performance.